2018
DOI: 10.1016/j.neuron.2018.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Potentiation Requires a Rapid Burst of Dendritic Mitochondrial Fission during Induction

Abstract: SUMMARY Synaptic transmission is bioenergetically demanding, and the diverse processes underlying synaptic plasticity elevate these demands. Therefore, mitochondrial functions including ATP synthesis and Ca2+ handling, are likely essential for plasticity. Although axonal mitochondria have been extensively analyzed, LTP is predominantly induced postsynaptically, where mitochondria are understudied. Additionally, though mitochondrial fission is essential for their function, signaling pathways that regulate fissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
111
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 88 publications
7
111
0
Order By: Relevance
“…Increased smaller size mitochondria is associated with enhanced fission, which mediates structural and synaptic plasticity (Cassidy-Stone et al, 2008;Chen et al, 2007;Divakaruni et al, 2018;Ishihara et al, 2009;Li et al, 2004). However, fission molecules, including Drp1 which is associated with enhanced structural and synaptic plasticity Divakaruni et al, 2018;Li et al, 2004), were similar between NAc MSN subtypes. Thus, the smaller mitochondria observed in D2 MSNs may represent reduced fusion as addressed above.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Increased smaller size mitochondria is associated with enhanced fission, which mediates structural and synaptic plasticity (Cassidy-Stone et al, 2008;Chen et al, 2007;Divakaruni et al, 2018;Ishihara et al, 2009;Li et al, 2004). However, fission molecules, including Drp1 which is associated with enhanced structural and synaptic plasticity Divakaruni et al, 2018;Li et al, 2004), were similar between NAc MSN subtypes. Thus, the smaller mitochondria observed in D2 MSNs may represent reduced fusion as addressed above.…”
Section: Discussionmentioning
confidence: 94%
“…D2-MSNs display increased sEPSC frequency in NAc core and shell (Ma et al, 2013); however, another study examining NAc MSN subtypes in prepubertal mice demonstrated reduced mEPSC frequency in D2-MSNs in NAc core (Willett et al, 2018). However, fission molecules, including Drp1 which is associated with enhanced structural and synaptic plasticity Divakaruni et al, 2018;Li et al, 2004), However, fission molecules, including Drp1 which is associated with enhanced structural and synaptic plasticity Divakaruni et al, 2018;Li et al, 2004),…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations